ENTRY CRITERIA AS PREDICTOR OF ACADEMIC SUCCESS: A CASE OF SOLUSI UNIVERSITY, ZIMBABWE - Awoniyi Samuel Adebayo; Awoniyi Tinuola Dorcas (European Scientific Journal, ESJ, 2014)
This study examined the predictive validity of entry criteria on academic success of students in the Faculty of Business Programmes at Solusi University. The predictors are the modes of entry and qualifications for admission into the university while the criterion is the Final Cumulative Grade Point Average (CGPA) at the end of university education. The sample for the study consisted of four hundred and sixty three (463) faculty of Business students who graduated in years 2007, 2008 and 2009. The stepwise regression was used for data analysis. The major findings of the study are that in general, ordinary level Mathematics and advanced level Accounts are predictors of academic success, and that the Cumulative Grade Point Average (CGPA) at the end of pre-university examination predicts academic success of the pre-university entrants.